(3JGQjN GdESdGe hWHbGJ GdeTGgjQ hGdCYdGes - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s
(3ChdgG (B:s
(3JHJOF HGdWHbI GdSGOS YTQI ef hajGJ SfI (B151 (3g` , bhdg (B: (3aJhai ajgG MfXdI Hf CHj Sfjf Gdeci , hOGhO Hf jRjO GdChOi , hSja Hf SdjeGf hajgG YRd YeQ Hf MaU GdegdHi Yf GdSfO s
(3BNQgG (B:s
(3jfJgi HYfhGf SfI KdGK hSJjf heFI (B: (3ajgG eGJ EHQGgje Hf WgeGf GdNQSGfi , hGQWGI Hf GdefdG GdMeUi SfI CQHY hSJjf heFI (B: (3ajgG eGJ ESMGb Hf jMji Hf WdMI GdTjei , hNQhL GHf UGdM GdeUQi hRjGO Hf s
(3HgG fXGe GdJYbjHIs
(3bWYI efgs
(3ef SfI (B151_ (3Chd SfI (B164s
(3cJHJ Hbde eged GdfbW CMjGfkG s
(3hajg VHW bdjd s
(3fSNI KGdKI s
Keywords: (3GdJGQjNs